Percepción de la violencia psicológica hacia la mujer en la relación de pareja y sexismo en adolescentes en acogimiento residencial: comparación con un grupo de adolescentes no institucionalizados - Jimeno Jiménez, María Verónica (Revista Española de Investigación Criminológica, 2020)
Exposure to violence during childhood can normalize perceptions of this type o conflict. Early intervention is key to preventing these attitudes from reproducing or suffering in youth or adulthood. The objective of this research is to analyse and compare the perception of violence against women in the relationship and the sexism of adolescents in Foster home with other non-institutionalized. A sample of 112 adolescents between 11 and 18 years old, (30% male and 60.6 % female), 34.8 % in residential care and 65,2 non-institutionalized have been administered the scale of perception of psychological violence in heterosexual juvenile dating relationships (VEC) and the scale of detection of sexist behaviours in adolescence (DSA). The results indicate that the perception of violence correlates with hostile a benevolent and total sexism, and adolescents in residential care obtained lower scores in general perception of gender violence and their dimensions of threats, isolation, disqualifications and sexual pressure; and higher scores in hostile, a benevolent and total sexism.